Analisis Peramalan Perubahan Pemanfaatan Lahan di Kota Nganjuk terkait Rencana Lokasi Interchange Jalan Tol Ngawi-Kertosono - Wahyudi, Eko (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
The study examines the effects of the Ngawiâ€Kertosono toll road interchange development planning to land use change in Nganjuk as an agricultural city using Delphi method through exploration of expert opinion. The study forecasted potential development such as housingâ€residential, tradeâ€service and industryâ€warehousing as a result from the development plan. Analysis showed that the plan rendered two implications. On the one hand it provided an increase in accesibility south of the toll road making development possible, on the other hand the north of the toll road might suffer development challenges due to loss of accessibility because the interchange was to only accommodate traffic from the south. Because of this, experts think that the north part of the toll road will suffer stagnance. All this demonstrate contradictory influence of development planning in the development of a region.